Hubungan Nutrien Pada Sedimen dan Penutupan Lamun Di Perairan Jepara - Sarah Nabilla; Retno Hartati; Ria Azizah Tri Nuraini (Universitas Diponegoro, 2019)
The availability of nutrients in seagrass beds can act as growth limiting factors. Absorption of nutrients in the water column is carried out by the leaves while the absorption of nutrients from the sediment is carried out by the roots but does not rule out the transport of nutrients by the roots will also arrive at the leaves of the seagrass. If the nutrient requirement is not met properly, then the growth will be disrupted. Like the difference in distribution and density of seagrass itself. Nutrient concentrations in waters vary. Nitrate and phosphate levels in the waters are strongly influenced by sources of organic material from outside/land (allochthonous) or from the water itself (autocthonous). This research was conducted with the aim of nothing: to determine the relationship between nutrient content (nitrate and phosphate) in sediment to seagrass cover in Teluk Awur and Pantai Blebak, JeparaData collection of seagrass and sediment was carried out on March 2018 in the waters of Teluk Awur and Blebak Beach, Kabupaten Jepara. Type identification, density, and coverage are carried out at the research location. Nitrate and phosphate analysis in sediments is carried out in Laboratorium Pengujian dan Peralatan. Based on the results of research that has been carried out, it can be concluded that there is a very strong positive relationship between nutrients and seagrass closure in the two research locations, each of which is 0.955 (91.1%) in Teluk Awur waters and 0.962 (92.6%) in Blebak Beach.Ketersediaan nutrien di perairan padang lamun dapat berperan sebagai faktor pembatas pertumbuhan. Penyerapan nutrien pada lamun pada kolom air dilakukan oleh daun sedangkan penyerapan nutrien dari sedimen dilakukan oleh akar namun tidak menutup kemungkinan pengangkutan nutrien oleh akar juga akan sampai pada bagian daun. Jika kebutuhan nutrien tidak terpenuhi dengan baik, maka pertumbuhannya mengalami gangguan. Seperti perbedaan sebaran dan kepadatan lamun itu sendiri. Konsentrasi nutrien di perairan bervariasi. Kadar nitrat dan fosfat di perairan sangat dipengaruhi oleh sumber bahan organik yang berasal dari luar/ daratan (allochthonous) maupun dari dalam perairan itu sendiri (autocthonous). Penelitian ini dilakukan dengan tujuan: untuk mengetahui hubungan antara kandungan nutrien (nitrat dan fosfat) pada sedimen terhadap tutupan lamun di Teluk Awur dan Pantai Blebak, Jepara. Identifikasi jenis, kepadatan dan penutupan dilakukan pada lokasi penelitian. Analisa nitrat dan fosfat dalam sedimen dilakukan di Laboratorium Pengujian dan Peralatan. Berdasarkan hasil penelitian yang telah dilakukan dapat di ambil kesimpulan bahwa terdapat hubungan sangat kuat positif antara nutrien dengan penutupan lamun pada dua lokasi penelitian, nilainya masing-masing sebesar 0,955 (91,1%) di Perairan Teluk Awur dan 0,962 (92,6%) di Pantai Blebak.